Providing a model of a hidden curriculum in medical majors with an emphasis on medical ethics - Amir Nahavandi Takab; Eskandar Fathi Azar; Zarrin Daneshvar Heris; Hossein Baghaei (Tabriz University of Medical Sciences, 2021)
Background: The "hidden" curriculum, alongside official education, can transfer ethical and professional values and principles to medical students and show them the importance of medical ethics. Ethical issues are essential factors influenced by the hidden curriculum in the medical educational system; these issues are also instruments for medical students as they develop their professionalism and idealism. The current study aims to provide an empirical study model of this hidden curriculum and its role in transferring knowledge of medical ethics. Methods: The current research is qualitative in the phenomenological type. The statistical population consisted of professors along with students in their fourth and upper years of various medical disciplines at the Tabriz University of Medical Sciences during 2019-2020. The sample group, according to the qualitative nature of the research, was compiled to a theoretical saturation to be 36 professors and students. The data were collected through semi-structured interviews. Analysis was done using thematic coding and Smith`s method. To maintain quality and accuracy, interview content was analyzed by two authors to reconstruct the reality. The data and their interpretation were then provided to the professors to confirm their accuracy. To ensure stability of the data, the interviews were conducted in a suitable atmosphere and in compliance with the interview conditions and isolated from bias and personal opinion. Results:A total of 67 concepts were extracted that were consequently categorized into five main themes: 1. Objectives and Curriculum; 2. Physical Space; 3. Backgrounds and Perspectives; 4. Laws and regulations; and, 5. Relationships. A model for studying students' experiences of the hidden curriculum and medical ethics was presented. Conclusion: Since medical professors and senior students are dealing with patient health, it is essential to acknowledge the concept of medical ethics as a "hidden" curriculum alongside scientific and professional issues in designing medical curriculum.